Identifikasi Jamur Trichophyton Rubrum pada Kuku Kaki Petugas Pengangkut Sampah di Dinas Permukiman dan Lingkungan Hidup - Suparyati Suparyati; Winarti Apriliani (LPPM Akademi Kebidanan Harapan Ibu Pekalongan, 2022)
Background: Trichophyton rubrum is one of the species of fungus the causes dermatofitosis. Dermatofitosis is a fungal disease that attacks tissues containing keratin in the nails, hair, and stratum corneum in the epidermis. Delivery workers are occupational hazard to health and safety because of their close contact with trash. This leaves the trashmen susceptible to fingernail mold infections. The sample used was the hoisting of a garbage workers at the residential and environmental services in rural districts. To find out the Trichophyton rubrum fungus in the toenails of the settlements and environment service in Pekalongan district. And to find out what the percentage of the Trichophyton rubrum fungus is in the toenails of the settlement and environment workers in Pekalongan district. The type of research used is descriptive using toenails. The sample used was the toenails of a garbage worker with a population of 13 people serving in the settlement and environment services in Pekalongan district with 13 samples. A macroscopic and microscopic examination of the media Sabouraud Dextrose Agar (SDA) from 13 toenails samples of the garbage carrier’s hoof found a positive effect on the Trichophyton rubrum fungus as many as 4 samples (30,77%) and negative effect on the Trichophyton rubrum fungus as many as 9 samples (69,23%). There’s a fungal infection of Trichophyton rubrum with 4 samples (30,77%) in the toenails of a garbage carrier.